Cost and management accounting - Drury, Colin (Australia : Cengage Learning Asia Pte Ltd, 2010)
This is a text for introductory courses on cost and management accounting. It provides coverage of the elementary principles and techniques of costing and management accounting, and concentrates on the typical syllabus of a first year BA course
1 Introduction to management accounting -- 2 An introduction to cost terms and concepts -- 3 Cost assignment -- 4 Accounting entries for a job costing system -- 5 Process costing -- 6 Joint and by-product costing -- 7 Income effects of alternative cost accumulation systems -- 8 Cost-volume-profit analysis -- 9 Measuring relevant costs and revenues for decision-making -- 10 Pricing decisions and profitability analysis -- 11 Activity-based costing -- 12 Decision-making under conditions of risk and uncertainty -- 13 Capital investment decisions: appraisal methods -- 14 Capital investment decisions: the impact of capital rationing, taxation, inflation and risk -- 15 The budgeting process -- 16 Management control systems -- 17 Standard costing and variance analysis 1 -- 18 Standard costing and variance analysis 2: Further aspects -- 19 Divisional financial performance measures -- 20 Transfer pricing in divisionalized companies -- 21 Cost management -- 22 Strategic management accounting -- 23 Cost estimation and cost behaviour -- 24 Quantitative models for the planning and control of stocks -- 25 The application of linear programming to management accounting
Includes bibliographical references.
Keywords: COST ACCOUNTING